Design, simulation, and experimental study of hydrostatic drive system for wide-span farming platform - Jiaxiang Ma; Hongfeng Yan; Rongxuan Li; Falian Li; Xianfa Fang (PLoS ONE, 2025)
A versatile, robotic, and multi-functional wide-span farming platform, commonly known as a gantry tractor, can reduce soil compaction and enhance field production efficiency. In order to meet the functional requirements of wide-span farming platforms to achieve various steering modes in both transverse and longitudinal driving modes, while also improving the flexibility and stability of the platform’s movement, a hydrostatic drive system was designed in this study based on an X-type dual-pump and four-motor system. The platform drive system adopts two variable pumps to drive four hydraulic motors, and the two pump–motor systems are distributed diagonally along the chassis. Each pump–motor system uses a flow diverter to prevent track slippage when the platform is driving. Mechanical analysis of the tracked platform while driving was first carried out. Based on the analysis results, the parameters of the main hydraulic components of the hydraulic drive system were calculated and selected. Then, the hydraulic drive system was modeled and simulated using the AMESim software. Finally, experiments were conducted under different driving conditions, including road tests in longitudinal mode and farmland tests in transverse mode. The experimental results showed that the hydraulic drive system exhibited a stable and synchronized performance. The average deviation rate of platform in longitudinal mode on cement roads was 5.0%. The deviation of the platform in transverse mode on dry and wet soil at the maximum driving speed were 6% and 2.1%, respectively. The test results demonstrated that the designed wide-span platform exhibited good driving stability, which validated the rationality of the design. These findings provide a reference for the improvement and optimization of wide-span farming platforms.